2020
DOI: 10.1002/jts.22449
|View full text |Cite
|
Sign up to set email alerts
|

Collective Trauma and Mental Health Hospitalization Rates Among Children in New York State, 1999–2013: Age, Period, and Cohort Effects

Abstract: Mental health hospitalization rates among U.S. children have been increasing locally and nationally in recent decades. Children in New York State (NYS) have also witnessed several collective traumatic events during the last two decades including the September 11, 2001, terrorist attacks (9/11), the Great Recession, and Hurricane Sandy (2012) and its aftermath. Decomposition of these rates into age, period, and cohort effects may help elucidate how large-scale collective traumatic events may be driving time tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(54 reference statements)
0
4
0
1
Order By: Relevance
“…It has been shown in other work that parental separation during adolescence may increase the risk of AS. Many studies have reported an association between teenagers’ psychological problems and hormones (i.e., their physical development) and learning stress, and suggest that parents play a vital role in teenagers’ psychological counseling [ 10 , 50 , 51 ]. Other studies have shown, moreover, that many teenagers, particularly girls, are likely to seek emotional communication and confide in their mothers [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in other work that parental separation during adolescence may increase the risk of AS. Many studies have reported an association between teenagers’ psychological problems and hormones (i.e., their physical development) and learning stress, and suggest that parents play a vital role in teenagers’ psychological counseling [ 10 , 50 , 51 ]. Other studies have shown, moreover, that many teenagers, particularly girls, are likely to seek emotional communication and confide in their mothers [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this outcome is, while primary school students may be less likely to experience (or able to report) AS during this time of their life, parental separation during this period may increase the risk of AS occurring in later childhood. Furthermore, many studies have reported an association between teenagers' psychological problems and hormones (i.e., their physical development) and learning stress, and suggest that parents play a vital role in teenagers' psychological counseling [21,79,80]. Other studies have shown, moreover, that many teenagers, particularly girls, are likely to seek emotional communication and con de in their mothers [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, no estado de Nova York aproximadamente 99% das hospitalizações tiveram como principal diagnóstico o transtorno depressivo, em estudo realizado com crianças internadas no intervalo de 1999 a 2013 (Liu & Lim, 2020).…”
Section: Discussionunclassified